The Routledge companion to literature and class - McMillan, Gloria (Professor) (New York, NY : Routledge, 2021)
"The Routledge Companion to Literature and Class offers a comprehensive and fresh assessment of the cultural impact of class in literature, analyzing various innovative, interdisciplinary approaches of textual analysis and intersections of literature, including class subjectivities, mental health, gender and queer studies, critical race theory, quantitative and scientific methods, and transnational perspectives in literary analysis. Utilizing these new methods and interdisciplinary maps from field-defining essayists, students will become aware of ways to bring these elusive texts into their own writing as one of the parallel perspectives through which to view literature. This volume will provide students with an insight into the history of the intersections of class, theory of class and invisibility in literature, and new trends in exploring class in literature. These multidimensional approaches to literature will be a crucial resource for undergraduate and graduate students in becoming familiar with class analysis, and offers seasoned scholars the most significant critical approaches in class studies"--
Keywords: Social classes in literature; Class consciousness in literature; Literature and society; LITERARY CRITICISM / General